Bulgarian Constitutional Identity: Problems and Possibilities - Asenov, Simeon (Research Papers, 2019)
The paper presents the substance and the practical dimensions of the concept “constitutional identity“ for the protection of the Bulgarian national sovereignty at the beginning of XXI century in times of increasing EU political integration. It also states a deficit of knowledge about the constitutional identity and its potential opportunities to limit the transfer of state sovereignty towards EU or other international organizations. In methodological aspect the paper uses the interdisciplinary approach that combines constitutional-legal and political analysis of the researched issue.
Keywords: Constitution; Constitutional identity; State system; Sovereignty; Council of Europe; Constitutional court; Judicial dialogue; European union; Lisbon treaty